Development of acoustic emission technology for condition monitoring and diagnosis of rotating machines: bearings, pumps, gearboxes, engines, and rotating structures - Mba, David; Rao, Raj B. K. N. (Vibration Institute (SAGE), 2006)
One of the earliest documented applications of Acoustic Emission Technology (AET) to rotating machinery monitoring was in the late 1960s. Since then there has been an explosion in research and application based studies covering bearings, pumps, gearboxes, engines and rotating structures. This paper presents a comprehensive and critical review to date on the application of Acoustic Emission Technology to condition monitoring and diagnostics of rotating machinery.
Proof pdf available on ResearchGate (2nd May 2015 uploaded by David Mba)